Electromagnetic loss in carbon based materials - Vovchenko, L.; Matzui, L.; Kototash, I.; Rzheshevska, O. (Functional Materials, 2006)
Paper presents the results of investigation of electromagnetic insertion loss (A) for carbon materials, including thermoexfoliated graphite (TEG), TEG-metal and TEG-epoxy composites (CMs) in temperature ranges 77-300 K at the frequency f≈1.8 GHz. The performed investigations have shown that TEG-based composite materials are prospective to use them as radio-protective materials in the electromagnetic shields for radio objects and buildings in particular. The microwave insertion loss L for studied TEG and TEG-Me based specimens at the frequency of 1.8 GHz is ranged within (16.2-18.5) dB. TEG-based composites containing polymer binder (epoxy resin) was shown to provide high electromag¬netic insertion loss (L = 23.5 dB) as well as high level of elastic-plastic parameters. The increase of microwave insertion loss A(L) is observed for all the studied CMs under decrease of temperature. But the character of A(T) was found to be essentially dependent on the type of CM.